2016
DOI: 10.5614/j.eng.technol.sci.2016.48.6.8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyhedral Magnetite Particles by Hydrothermal Process under High Pressure Condition

Abstract: Abstract. Magnetite particles were successfully generated by hydrothermal synthesis using water at subcritical conditions. By changing the temperature and pressure at subcritical water conditions, the thermodynamics and transport properties of the water can be controlled, thus enabling to manage the way of crystal formation, morphology, and particle size. In this work, the experiments were carried out at temperatures of 250 °C and 290 °C and a pressure of 10 MPa with a reactor made of SUS 316 in a batch system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[17][18][19] Nevertheless, recent advancement of extraction technology revealed that subcritical water or ionic liquid which act as a good hydrogen donor solvent, could effectively recover polyphenolic compounds from lignocellulosic biomass or plant material using hydrothermal treatment. [20][21][22] This study was focused on the investigation of rutin recovery from the crude extract of Labisia pumila var. Alata using different percentages of methanol as the eluent in C18 reversed phase SPE.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Nevertheless, recent advancement of extraction technology revealed that subcritical water or ionic liquid which act as a good hydrogen donor solvent, could effectively recover polyphenolic compounds from lignocellulosic biomass or plant material using hydrothermal treatment. [20][21][22] This study was focused on the investigation of rutin recovery from the crude extract of Labisia pumila var. Alata using different percentages of methanol as the eluent in C18 reversed phase SPE.…”
Section: Introductionmentioning
confidence: 99%